1982
DOI: 10.5962/bhl.title.46619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beach nourishment and borrowing on marine organisms / by Syed M. Naqvi and Edward J. Pullen.

Abstract: Approved for public release; distribution unlimited. 17. DISTRIBUTION STATEMENT (of tha abatract entarad In Block 20, 11 dlllerent Irom Report) 18. SUPPLEMENTARY NOTES 19. KEY WORDS (Conlinu avaraa aida II nacaaaary and Identify by block number) Beach nourishment Benthic communities Borrow areas Corals Fish Impacts Sea turtles 20. ABSTRACT rCbntfilu*. Tarn at^B If najc aa aary and Idenllfy by block ntimbar) This report summarizes the latest research on the effects of beach nourishment and borrowing on the coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[1] However, restrictions imposed to gasoline in order to enhance fuels quality, force to reduce the benzene content decreasing the impact on human health and environment. [2,3] Besides gasoline, benzene is one of the most common aromatic petrochemicals in the chemical industry, with diverse applications and a large commercial value. Among its uses, benzene plays an important role as solvent in paints or as intermediate chemical DOI: 10.1002/adts.201900112 product in the manufacture of plastics, drugs, dyes, detergents, and insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, restrictions imposed to gasoline in order to enhance fuels quality, force to reduce the benzene content decreasing the impact on human health and environment. [2,3] Besides gasoline, benzene is one of the most common aromatic petrochemicals in the chemical industry, with diverse applications and a large commercial value. Among its uses, benzene plays an important role as solvent in paints or as intermediate chemical DOI: 10.1002/adts.201900112 product in the manufacture of plastics, drugs, dyes, detergents, and insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was shown that IONP can provide some cytotoxic effects, such as local and systemic inflammation, oxidative stress, genotoxicity and others. [4,5] These effects can be explained by the high amount of Fe 2+ /Fe 3+ ions exposed on the large surface area of iron oxide nanoparticles. These ions can accept or donate electrons with following the formation of different free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…To put the legal discourse into action, frameworks for implementation are required, which are often not in place or have loopholes that can easily be manipulated against the victims. In her pursuit of justice, a female survivor of violence has to approach a combination of laws, systems and procedures -all engrained in the highly patriarchal moral code of Pakistan's society and shaped by systematic misogyny (Naqvi and Syed 2015). At every step, from filing a case to the rounds of visits for the sluggish judicial process, barriers arise that not only question a victim's credibility and repute, but also sometimes lead to withdrawal of the case.…”
Section: Access To Justicementioning
confidence: 99%